Association between subjective memory complaints and depressive symptoms after adjustment for genetic and family environmental factors in a Japanese twin study - Tanaka, Haruka (Environ Health Prev Med, 2015)
OBJECTIVES: The aim of this study was to investigate the association between subjective memory complaints (SMCs) and depressive symptoms, with and without adjustment for genetic and family environmental factors. METHODS: We conducted a cross-sectional study using twins and measured SMCs and depressive symptoms as outcomes and explanatory variables, respectively. First, we performed regression analyses using generalized estimating equations to investigate the associations between SMCs and depressive symptoms without adjustment for genetic and family environmental factors (individual-level analyses). We then performed regression analyses for within-pair differences using monozygotic (MZ) and dizygotic (DZ) twin pairs and MZ twin pairs to investigate these associations with adjustment for genetic and family environmental factors by subtracting the values of one twin from those of co-twin variables (within-pair level analyses). Therefore, differences between the associations at individual- and within-pair level analyses suggested confounding by genetic factors. RESULTS: We included 556 twins aged ≥20 years. In the individual-level analyses, SMCs were significantly associated with depressive symptoms in both males and females [standardized coefficients: males, 0.23 (95 % CI 0.08–0.38); females, 0.35 (95 % CI 0.23–0.46)]. In the within-pair level analyses using MZ and same-sex DZ twin pairs, SMCs were significantly associated with depressive symptoms. In the within-pair level analyses using the MZ twin pairs, SMCs were significantly associated with depressive symptoms [standardized coefficients: males, 0.32 (95 % CI 0.08–0.56); females, 0.24 (95 % CI 0.13–0.42)]. CONCLUSIONS: This study suggested that SMCs were significantly associated with depressive symptoms after adjustment for genetic and family environmental factors.